2019
DOI: 10.1111/tmi.13244
|View full text |Cite
|
Sign up to set email alerts
|

Forest disturbance and vector transmitted diseases in the lowland tropical rainforest of central Panama

Abstract: Objective To explore possible changes in the community attributes of haematophagous insects as a function of forest disturbance. We compare the patterns of diversity and abundance, plus the behavioural responses of three epidemiologically distinct vector assemblages across sites depicting various levels of forest cover. Methods Over a 3‐year period, we sampled mosquitoes, sandflies and biting‐midges in forested habitats of central Panama. We placed CDC light traps in the forest canopy and in the understorey to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
2
10
1
Order By: Relevance
“…, 25 However, the role of Ps. thula as a vector of Leishmania (V) panamensis , the main parasite causing ACL in Panama, has still not been confirmed, 12 , 24 , 26 and it was not supported by our results either. Ny.…”
contrasting
confidence: 78%
“…, 25 However, the role of Ps. thula as a vector of Leishmania (V) panamensis , the main parasite causing ACL in Panama, has still not been confirmed, 12 , 24 , 26 and it was not supported by our results either. Ny.…”
contrasting
confidence: 78%
“…The effects of anthropogenic disturbance could also impact avian haemosporidian infection dynamics by differentially affecting the vectors of Haemoproteus and Plasmodium . For example, in a recent study Loaiza et al, (2019) have shown that while Culicoides were mainly classified as climax (i.e. forest specialists), a significant portion of mosquito species were classified as colonists (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the biodiversity of mosquito species and their association with anthropogenic actions and forest area is important for increasing the knowledge of the possible changes in mosquito populations and pathogen transmission [30,31]. The diversity of avian haemosporidian vectors remains poorly studied in the Neotropical region and, more specifically, in the Atlantic Forest.…”
Section: Discussionmentioning
confidence: 99%